Environmental Sustainability: Event Inauguration Of Tourism Village As An Initial Stage In The Built Environment - Alnuron, Arvid; Romizal, Alba; Andari, Rini (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to see how the steps taken by the management of the tourism village to preserve the natural environment, community empowerment in the embung puri idaman tourism village, this is important to know because looking at the conditions in the embung puri idaman tourism village it looks a lot of deforested land. The inauguration of the Tourism Village is a formality activity that initiates the steps of the management of the dream puri embung tourism village to preserve the natural environment and community empowerment. This research was conducted with a qualitative approach of Interview, Observation to answer research problems. Based on the findings in the field and interviews with the interviewees, the speakers found found that the management of Embung Puri Idaman Village has good steps in preserving the environment. The step taken by the manager is to combine the inauguration of the dream embung puri tourism village with the program of planting fruit types planted on barren land. The impact of environmental sustainability is as a management tourism village and the surrounding community has plantation land produced and has income for tourism villages and helps the community as sellers around the ideal embung puri tourism village, besides that it is important to maintain environmental sustainability to be useful even more. Implications for education are new science, for practitioners in the field is an addition to management science